MITA/STING and Its Alternative Splicing Isoform MRP Restrict Hepatitis B Virus Replication. - Shuhui Liu; Kaitao Zhao; Xi Su; Lu Lu; He Zhao; Xianwen Zhang; Yun Wang; Chunchen Wu; Jizheng Chen; Yuan Zhou; Xue Hu; Yanyi Wang; et al. (PLoS ONE, 2017)
An efficient clearance of hepatitis B virus (HBV) requires the coordinated work of both the innate and adaptive immune responses. MITA/STING, an adapter protein of the innate immune signaling pathways, plays a key role in regulating innate and adaptive immune responses to DNA virus infection. Previously, we identified an alternatively spliced isoform of MITA/STING, called MITA-related protein (MRP), and found that MRP could specifically block MITA-mediated interferon (IFN) induction while retaining the ability to activate NF-κB. Here, we asked whether MITA/STING and MRP were able to control the HBV replication. Both MITA/STING and MRP significantly inhibited HBV replication in vitro. MITA overexpression stimulated IRF3-IFN pathway; while MRP overexpression activated NF-κB pathway, suggesting these two isoforms may inhibit HBV replication through different ways. Using a hydrodynamic injection (HI) mouse model, we found that HBV replication was reduced following MITA/STING and MRP expression vectors in mice and was enhanced by the knockout of MITA/STING (MITA/STING-/-). The HBV specific humoral and CD8+ T cell responses were impaired in MITA/STING deficient mice, suggesting the participation of MITA/STING in the initiation of host adaptive immune responses. In summary, our data suggest that MITA/STING and MRP contribute to HBV control via modulation of the innate and adaptive responses.